2020
DOI: 10.1007/s00520-020-05886-z
|View full text |Cite
|
Sign up to set email alerts
|

Returning to work in lung cancer survivors—a multi-center cross-sectional study in Germany

Abstract: Purpose To investigate the work situation of lung cancer survivors and to identify the factors associated with their returning to work. Methods Descriptive analysis and logistic regression were used to evaluate study population characteristics and independent factors of subsequently returning to work. To analyze time to return to work, Cox regression was used. Results The study sample included 232 lung cancer survivors of working age from 717 enrolled participants in the multi-center cross-sectional LARIS (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 38 publications
(74 reference statements)
3
25
1
2
Order By: Relevance
“…Earle and his colleagues reported only 21% of lung cancer survivors remained employed in the 15 months after their cancer diagnosis [ 27 ]. A recent cross-sectional study from Germany revealed a 33% employment rate within 1 year after being diagnosed with lung cancer [ 28 ]. Our study found a 41% employment rate in the fifth year of the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Earle and his colleagues reported only 21% of lung cancer survivors remained employed in the 15 months after their cancer diagnosis [ 27 ]. A recent cross-sectional study from Germany revealed a 33% employment rate within 1 year after being diagnosed with lung cancer [ 28 ]. Our study found a 41% employment rate in the fifth year of the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, primary lung cancer survivors and patients who had survived at least one year after the diagnosis were enrolled. Further inclusion criteria were: (1) at least 18 years of age, (2) lung cancer-related admission to the hospital between 2004 and 2014, and (3) being mentally and verbally able to take part in a telephone interview in German (Eichler et al 2018 ; Hechtner et al 2019 ; Rashid 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 50% of cancer patients are employed at the time of diagnosis so returning to work is an important issue (7)(8)(9)(10)(11) . Working has been pointed out by several authors as of key importance (11)(12)(13) since it relates to self-efficacy, belonging, and financial security (10,14) .…”
Section: Introductionmentioning
confidence: 99%